What about those long, "barky" nights? - Williamson, Janielee (Canadian Journal of Emergency Nursing, 2005)
This article was submitted by Janielee Williamson, RN, Cochrane, Alberta. Janie is the project coordinator for a multi-centre research project across Alberta looking at the best method for disseminating practice guidelines to physicians. The project personnel are working in collaboration with the Alberta Medical Association CPG Committee to determine which method improves the delivery of best practice for children with croup, while ensuring optimum care for the child and determining which method has the best overall benefit for the health care system and the family. All emergency department personnel are familiar with this scenario: 18-month-old boy presents to the emergency department at 2 a.m. on December 18. Parents look worried, yet they are baffled. As they tell their story, they are almost apologetic, “Really, he was much worse at home, he seems so much better since we drove to the hospital. He woke up in distress, he couldn’t breathe and he was making this awful noise when he took a breath in. And his cough – I’ve never heard anything like it – he sounded like a dog... or no, more like a seal. Really, it was terrible!” There, in mom’s arms, is a happy, quiet boy looking around. When you try to examine him, his cry is stridorous and you hear the bark... reassuringly you smile back at the mom. “Yes, we know, and no we don’t have magic doors. HE HAS CROUP.”